2003
DOI: 10.1017/s0967199403002302
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural localisation of calcium deposits in pig oocytes maturing in vitro: effects of verapamil

Abstract: The culture of pig oocytes in the presence of the calcium channel blocker verapamil (0.02 mM) resulted in the blocking of meiosis at the metaphase I stage, and only a small fraction (about 28%) of the oocytes were able to continue their maturation to the stage of metaphase II. Hence, meiotic maturation in pig oocytes is a calcium-dependent process. After isolation of the pig oocytes from their follicles, the intracellular calcium deposits in the oocyte and granulosa cells, detectable using the combined oxalate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…Moreover, the effects of cypermethrin, deltamethrin and fenvalerate on ion channels can be due to the inhibition of calcineurin, which is involved in the regulation of calcium channels (Yakel, 1997). In our previous studies (Rozinek et al, 2003) we observed delayed maturation of fully grown pig oocytes with full meiotic competence after specific inhibition of L-type calcium channels. Of course, we cannot exclude other effects of calcineurin inhibitors.…”
Section: Discussionmentioning
confidence: 85%
“…Moreover, the effects of cypermethrin, deltamethrin and fenvalerate on ion channels can be due to the inhibition of calcineurin, which is involved in the regulation of calcium channels (Yakel, 1997). In our previous studies (Rozinek et al, 2003) we observed delayed maturation of fully grown pig oocytes with full meiotic competence after specific inhibition of L-type calcium channels. Of course, we cannot exclude other effects of calcineurin inhibitors.…”
Section: Discussionmentioning
confidence: 85%
“…Further, drugs that induce Ca ++ release from internal store (calcium ionophore A23187 (CI) and ionomycin) can also trigger meiotic resumption from diplotene arrest in mouse (Jones et al, ; Lefevre et al, ; Wakai et al, ), rat (Chaube et al, ), bovine (Boni et al, ), porcine (Fan et al, ), and human oocytes cultured in vitro (Lu et al, ). The Ca ++ channel blockers (verapamil and nifedipine) inhibit spontaneous resumption of meiosis in mouse (Homa, ), rat (Paleos and Powers, ; Yoo and Smith, ), porcine (Bae and Channing, ; Rozinek et al, ), and bovine oocytes cultured in vitro (Tosti et al, ). Previous study has revealed that increased Ca ++ oscillations within the oocyte trigger meiotic resumption from diplotene arrest (Fan et al, ).…”
Section: Role Of Ca++ In Meiotic Resumption From Diplotene Arrestmentioning
confidence: 99%
“…On the other hand, use of nifedipine and ruthenium red in culture medium can protect oocytes undergoing postovulatory aging‐induced SOA to increase the number of M‐II arrested oocytes required for various assisted reproductive technology (ART) program (Yoo and Smith, ; Premkumar and Chaube, ). The Ca ++ channel blockers such as verapamil inhibit spontaneous meiotic resumption in mouse (Homa, ), rat (Paleos and Powers, ; Chaube et al, ), bovine (Tosti et al, ), and porcine oocytes (Bae and Channing, ; Rozinek et al, ). Studies suggest that lower doses of verapamil may be used to inhibit spontaneous parthenogenetic activation and facilitate an availability of more number of M‐II arrested oocytes for rat cloning by somatic cell nuclear transfer protocol (Chaube et al, ; Premkumar and Chaube, ).…”
Section: Role Of Ca++ In Meiotic Resumption From Diplotene Arrestmentioning
confidence: 99%
“…A certain amount of calcium ions can enter the oocyte from the extracellular milieu even after treatment with verapamil. However, L-type calcium channels evidently play an important role in pig oocytes, because their blockage using verapamil induces a block of meiotic maturation (Kaufman and Homa, 1993) and results in an abnormal distribution of intracellular calcium stores (Rozinek et al, 2003). Based on data from the experiment performed by Petr et al (2005b), it can be concluded that the function of the L-type calcium channel also plays a key role in the parthenogenetic activation of pig oocytes using the NO-donor treatment.…”
Section: What Role Is Played By Calcium In No-dependent Oocyte Activamentioning
confidence: 99%
“…The effects of protein kinase G close the ion channels through which free calcium ions entered the cell from extracellular spaces (Alioua et al, 1998;Fukao et al, 1999). Various types of these channels are expressed in mammalian oocytes (Lee et al, 2004a) and it is clear that their function is essential for meiosis especially in pig oocytes (Kaufman and Homa, 1993;Rozinek et al, 2003). We cannot exclude a possibility that nitric oxide also regulates the activation of oocytes through processes which does not depend on cGMP.…”
Section: Which Processes Are Specific To No-induced Oocyte Activation?mentioning
confidence: 99%